2019
DOI: 10.3390/jfmk4030046
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Chronic Achilles Tendinopathy: A Systematic Review

Abstract: Achilles tendinopathy is a common musculoskeletal disorder. Athletes, runners and jumpers, and the sedentary are frequently affected. Numerous are the therapeutic choices to manage these kinds of disorders. The aim of this review is to analyze the available literature to document the up-to-date evidence on conservative management of Achilles tendinopathy. A systematic review of two medical electronic databases was performed by three independent authors, using the following inclusion criteria: conservative trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…The rehabilitation team made up of medical doctors, physiotherapists and athletic trainers should work in synergy, sharing a timeline and short, medium, and long-term goals for a complete recovery. The patient with AT should start an early rehabilitation program, under physiotherapist supervision, including eccentric exercises whose effectiveness has been demonstrated, indeed a recent systematic review confirmed that among the several conservative treatments of AT, the only one universally accepted as a gold standard is the eccentric exercise widely used in the clinical trials included in the review [86]. In addition to physical exercise, other conservative therapies can be used, such as the use of ESWT, physical therapies and the use of injections.…”
Section: Discussionmentioning
confidence: 94%
“…The rehabilitation team made up of medical doctors, physiotherapists and athletic trainers should work in synergy, sharing a timeline and short, medium, and long-term goals for a complete recovery. The patient with AT should start an early rehabilitation program, under physiotherapist supervision, including eccentric exercises whose effectiveness has been demonstrated, indeed a recent systematic review confirmed that among the several conservative treatments of AT, the only one universally accepted as a gold standard is the eccentric exercise widely used in the clinical trials included in the review [86]. In addition to physical exercise, other conservative therapies can be used, such as the use of ESWT, physical therapies and the use of injections.…”
Section: Discussionmentioning
confidence: 94%
“…The reason of the ESWT beneficial action could be detected in the mechanical stimulus provided, which promotes increased pro-inflammatory mediators such as interleukins and metalloproteases [11]. Waugh et al analyzed the in vivo the biological response to extracorporeal shockwaves, and they showed that in the dialysate tendon, there were some predominant cytokines, some of which had an elevated concentration immediately after ESWT, and then remained significantly elevated for several hours post-ESWT [25].…”
Section: Discussionmentioning
confidence: 99%
“…ESWT has become a widely employed approach in different musculoskeletal pathologies, including the upper limb soft tissues diseases [9], chronic Achilles tendinopathy [10] and plantar fasciitis [11]. Although the therapeutic mechanism of this treatment is controversial, some studies suggested that the shear stress and compression forces induced and maintained by ESWT should stimulate the extracellular matrix binding proteins and endothelial cell homeostasis and the reaction of the bonelacuno-canalicular [12], which should promote the neovascularization, improve angiogenesis, enhance tissue perfusion and reduce the necrotic zone and tissue apoptosis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they have good application prospects. At present, the most difficult problem with the action of growth factors at sites of injury is the difficulty associated with achieving their sustained and controllable release and the control of the inflammatory response after the stent enters the body [ 173 ]. The combination of biomimetic nanoparticles (NPS) and scaffolds represents a new approach to promoting the sustained and effective release of drugs and growth factors [ 174 ].…”
Section: Biological Factors For Repairing Tendons and Ligamentsmentioning
confidence: 99%